Discrepancy between Visual Acuity and Microperimetry in AMD Patients: Visual Acuity Appears as an Inadequate Parameter to Test Macular Function - Tran, B.-K.; Herbort, C. P., Jr. (Klinische Monatsblätter für Augenheilkunde, 2015)
Background: Best corrected visual acuity (BCVA) of 0.8 or above in AMD patients can sometimes correspond to poor macular function inducing a serious visual handicap. Microperimetry can be used to objectivize this difference.Patients and Methods: A retrospective study was undertaken on 233 files of AMD patients of whom 82 had had a microperimetry. BCVA was compared with microperimetry performance. All examinations were performed in an identical setting by the same team of 3 persons.Results: Among the 82 patients included, 32 (39.0 %) had a BCVA equal to or above 0.8 even though their microperimetry performance was lower than 200/560 db. 10 of them (12.2 % of total) had an even poorer microperimetry below 120/560 db indicating poor macular function.Conclusions: More than a third of the AMD patients had a bad or very bad microperimetry performance in parallel with a good visual acuity. Microperimetry is a valuable tool to assess and follow real macular function in AMD patients when visual acuity alone can be misleading.
Keywords: altersbedingte Makuladegeneration; makuläre Funktion; Visusmessung; Mikroperimetrie; Diskrepanz